Pharmacogenomics and pharmacokinetics of antiretroviral drugs and their associations with metabolic complications in HIV-infected Black South Africans - Sinxadi, Phumla Z (Division of Clinical Pharmacology, 2016)
BACKGROUND: Antiretroviral therapy (ART), notably efavirenz and lopinavir, have been associated with metabolic abnormalities known to increase cardiovascular risk. Efavirenz and lopinavir pharmacokinetics demonstrate considerable interindividual variability, which in part, may be explained by host genetic factors. Mitochondrial DNA (mtDNA) variation influences ART related metabolic complications. However, the associations between genetic polymorphisms and pharmacokinetics of antiretroviral drugs, and their associations with metabolic complications, are incompletely understood. We explored associations of mitochondrial DNA (mtDNA) haplogroups and ART related metabolic complications, characterized relationships between genetic polymorphisms and plasma efavirenz concentrations, and investigated associations between plasma efavirenz/lopinavir concentrations and lipid and glucose concentrations in HIVinfected Black South Africans. METHODS: We collected clinical and laboratory data from HIV infected patients on ART from Cape Town. We sequenced the mitochondrial genome and determined African mtDNA haplogroups. We genotyped 241 polymorphisms in genes potentially relevant to efavirenz metabolism and transport. We measured steady state efavirenz and lopinavir concentrations and used regression analyses to determine associations with metabolic parameters.